217k views
1 vote
-4 + (-8) - (-2) + 4

User Eddym
by
5.3k points

2 Answers

7 votes

Answer:

Hi there!

The answer to this question is -6.

Explanation:

-4 + -8 = -12

-12 - (-2) is equivalent to -12 + 2 which equals -10

then -10 + 4 equals -6

therefore the final answer is -6

User Mic Fok
by
5.3k points
7 votes

Answer:

-6

Explanation:

-4+ -8 = -12 +2 = -10 +4 = -6

User Glade Mellor
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.